2012
DOI: 10.1093/nar/gks971
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the DNA-binding activity of the human ERG transcription factor using new heterocyclic dithiophene diamidines

Abstract: Direct modulation of gene expression by targeting oncogenic transcription factors is a new area of research for cancer treatment. ERG, an ETS-family transcription factor, is commonly over-expressed or translocated in leukaemia and prostate carcinoma. In this work, we selected the di-(thiophene-phenyl-amidine) compound DB1255 as an ERG/DNA binding inhibitor using a screening test of synthetic inhibitors of the ERG/DNA interaction followed by electrophoretic mobility shift assays (EMSA) validation. Spectrometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 51 publications
1
67
0
Order By: Relevance
“…S3B). Among them, according to Nhili and colleagues’ study (34), only two (positions −1050bp and −314 bp) were characterized by strong flanking sequences (black asterisks in Fig. 2A).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…S3B). Among them, according to Nhili and colleagues’ study (34), only two (positions −1050bp and −314 bp) were characterized by strong flanking sequences (black asterisks in Fig. 2A).…”
Section: Resultsmentioning
confidence: 91%
“…Asterisks indicate the most probable ERG binding sites according to Nihil and colleagues (34). Purple arrows indicate the two regions of CHK1 promoter identified by Yu and colleagues in a ChIP-seq analysis for ERG (21).…”
Section: Figurementioning
confidence: 99%
“…The EBD is an 85 amino-acid domain that forms a winged helix-turn-helix motif that binds to DNA sequences that contain a core GGAA/T sequence (18). ERG has been shown to bind to this core sequence (19).…”
Section: Resultsmentioning
confidence: 99%
“…Another gene that is being targeted 1215 for cancer therapy is ERG transcription factor, the gene 1216 with the most significant copy number gain in our anal-1217 ysis. Several studies have reported their attempts in de-1218 veloping drugs that target the ERG transcription fac-1219 tor, mostly in prostate cancer [244,245]. Further vali-1220 dation of the results described here would suggest the 1221 expansion of such trials to include melanoma.…”
mentioning
confidence: 78%